Effects of habit-breaking appliances on tongue movements during deglutition in children with tongue thrust swallowing using ultrasonography - A pilot study - Mihir Nayak; Sandya Devi S Patil; Madhu Kakanur; Snehalika A More; S Ravi Kumar; Rachna Thakur (Wolters Kluwer Medknow Publications, 2020)
Objective: The aim of this study is to evaluate and compare the duration and range of tongue movements in tongue thrust swallow patterns with and without habit-breaking appliances using computer-aided M-mode ultrasound images. Also to record the corresponding position of the tongue associated with normal and tongue thrust swallowing pattern using B-mode ultrasound images. Methodology: Ten patients with mature swallow pattern, ten subjects with anterior tongue thrust (ATT) and ten patients with lateral tongue thrust (LTT) swallowing habit were analyzed for the duration and range of tongue movement using two-dimensional ultrasound M-mode images before and after insertion of three habit-breaking appliances (anterior tongue crib [ATC], double oral screen [DOS] and DeLuke oral trainer [DOT]). Further, B-mode images were examined for the tongue positions in different swallow patterns with and without appliances. Results: Duration and range of tongue movement for the entire swallowing phase did not show a statistically significant difference for mature, ATT and LTT. Statistical significant difference existed in the duration between ATC and DOS with DOT for ATT patient (P = 0.05). Furthermore, a significant difference existed in the range of tongue movement between DOS and DOT in LTT patients (P = 0.05). Conclusion: Remarkable changes in the tongue position were observed postinsertion of DOT in both anterior and LTT swallow patterns where the tongue tip and anterior tongue dorsum shifted upward toward the anterior palate resembling that of a mature swallow pattern.